Prevalence of intestinal parasites in the healthy adult and adolescent population of a rural community - Hyder, S.M. Ziauddin (BRAC Research and Evaluation Division (RED), 2019)
To study the prevalence of intestinal worm infestations among the healthy adult rural populatio~ 333 stool samples were coHected form 8 villages under Fulbaria thana of Mymensingh district by systematic random sampling technique. Stool samples were examined under microscope for the presence of intestinal parasites. The gross prevalence of parasites was 33.3% of which 35.8% were in females and 27.9% in males. Significant difference of intestinal parasite infestation was observed in different age group and the highest prevalence (40%) was found among the age group of 18-35 years. Significant association was found been hand washing with soap and prevalence of intestinal parasite infestation (p<0.05).